Analysis Of Attentuation In The System Of Communication Of Optical Fiber - Mooniarsih, Neilcy T; Srihendayana, Hidayat; Sufandi, M. Ridhwan (ELKHA : Jurnal Teknik Elektro, 2012)
Abstract The research is on the use of optical fiber as a medium of transmission in form of optical wave (light), namely, G. 652 SMF and G.655 SMF NZDS, in Link Main Route and Link Diversity Route. Optical fiber also experiences losses. One of them is attentuation or the decrease of the light due to the distance and characteristic of the fiber. The value of the attentuation is measured by using Optical Power Meter and OTDR YOKOGAWA AQ7275. The result of the measurement is compared with the standard stipulated by International Telecommunication Union (ITU). Through the comparison, it is known that most of the values of the attentuation of the optical fiber is under the standards of ITU. It means optical fiber used is in good condition, except in Link Diversity Route in Core 22 and Core 23 due to bending in the distance 13 kms and 17 kms from the Link Main Route. And, to know the performance of system of the optical fiber communication, the method of Link Power Budget is employed. Keywords Optical Fiber, Attentuation of Optical Fiber, Link Power Budget